2013
DOI: 10.1007/s00535-013-0890-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed microRNAs in human hepatocellular adenoma associated with type I glycogen storage disease: a potential utility as biomarkers

Abstract: We make the first observation of distinct miRNA deregulation in HCA associated with GSD Ia. We also provide evidence that miR-130b could serve as a circulating biomarker for detection of GSD Ia HCA. This work provides prominent candidate miRNAs worth evaluating as biomarkers for monitoring the development and progress of liver tumors in GSD Ia patients in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…2). These miRNAs have previously been shown to be linked to the pathogenesis of HCC and other types of cancer (Chiu et al, 2014, Karakatsanis et al, 2013, Murria Estal et al, 2013, Wang et al, 2012, Wong et al, 2011. Among the six miRNAs examined, the expression levels of four matched the microarray results (p< 0.05), warranting further study using a larger cohort of HCC clinical…”
Section: Mirna Expression Is Altered In Hccmentioning
confidence: 58%
See 1 more Smart Citation
“…2). These miRNAs have previously been shown to be linked to the pathogenesis of HCC and other types of cancer (Chiu et al, 2014, Karakatsanis et al, 2013, Murria Estal et al, 2013, Wang et al, 2012, Wong et al, 2011. Among the six miRNAs examined, the expression levels of four matched the microarray results (p< 0.05), warranting further study using a larger cohort of HCC clinical…”
Section: Mirna Expression Is Altered In Hccmentioning
confidence: 58%
“…Recently, it has been reported that deregulation of miRNA expression contributes to the development of different types of human cancers. Data from numerous studies also supported the notion that miRNAs could serve as prognostic and diagnostic markers of cancer (Callegari et al, 2014, Chiu et al, 2014.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…It may indicate that different test methods might partly lead to the discordance of different results. In addition, Chiu et al (2014) observed high levels of miR-34a expression in GSD Ia HCA. We speculate that miR-34a regulation in HCC might be complicated than once thought, which needs further experimentations and repeat efforts.…”
Section: Discussionmentioning
confidence: 87%
“…Five studies about hepatocellular carcinoma focused on miR-34a expressions which were found to be up-regulated in three results (Meng et al, 2007;Pineau et al, 2010;Chiu et al, 2014) and down-regulated in another two (N. Li et al, 2009;Dang et al, 2013), and average FC was 3.41 and − 1.61 respectively. Coincidentally, the results acquired from different detection methods seemed to approach from different ends.…”
Section: Discussionmentioning
confidence: 98%
“…miR34a was dramatically reduced or silenced in a large portion of clinical samples from patients with HCC (30)(31)(32). Because miR34a functions as an effective suppressor of malignant properties in cancers (9-13), reexpression of miR34a in tumors represents a potential approach for HCC treatment.…”
Section: Mir34a Modulator Inhibited Proliferation and Induced Apoptosmentioning
confidence: 99%